Foamy gland high-grade prostatic intraepithelial neoplasia on core biopsy and subsequent radical prostatectomy: An in depth case report of a rare variant - Paul Friedman, MD; Daniel Costa, MD; Payal Kapur, MD (Elsevier, 2017)
A 69-year-old man underwent a robotic-assisted laparoscopic prostatectomy after a biopsy proven diagnosis of prostatic adenocarcinoma (PCa). Both the biopsy and the prostatectomy specimens revealed an organ-confined conventional PCa of Gleason score 3 + 4 = 7 involving the left posterior lobe. In addition, the right lateral lobe revealed a separate large focus of high-grade prostatic intraepithelial neoplasia (HGPIN) involving enlarged, pale glands with tufted and micropapillary architecture. The neoplastic cells shared cytology of foamy gland carcinoma and had pseudostratified, small to pyknotic nuclei and abundant xanthomatous cytoplasm. Immunohistochemistry revealed positive racemase expression in the acinar cells, and basal cells were highlighted by p63 and high molecular weight cytokeratin, confirming a diagnosis of foamy gland HGPIN. No invasive foamy gland carcinoma was identified. Foamy gland HGPIN has limited mention in the literature and can easily be missed. Knowledge and recognition of this rare variant of HGPIN may be of significance in core biopsies in the absence of PCa. HGPIN is regarded as a precursor of PCa. Interestingly, both the foamy gland HGPIN and invasive conventional PCa showed ERG overexpression, however, only HGPIN showed loss of PTEN. Keywords: Prostate, Foamy gland, HGPIN